1984
DOI: 10.1038/307460a0
|View full text |Cite
|
Sign up to set email alerts
|

L-Glutamate has higher affinity than other amino acids for [3H]-D-AP5 binding sites in rat brain membranes

Abstract: Electrophysiological studies indicate the existence of several types of receptors for excitatory amino acids. Thus, responses induced by N-methyl-D-aspartate (NMDA) are potently and selectively blocked by D(-)-2-amino-5-phosphonopentanoic acid (D-AP5), while responses induced by such agonists as kainate and quisqualate are relatively resistant to this antagonist. Evidence is mounting that excitatory amino acid receptors are involved in synaptic excitation in many regions of the central nervous system (see refs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(121 citation statements)
references
References 16 publications
12
109
0
Order By: Relevance
“…Although the binding data of Olverman et al (1984) suggest that the affinity of glutamate for D-APV binding sites approaches that of D-APV itself, we think it likely that these high concentrations of APV or D-APV effectively blocked 500 PM glutamate from activating most of the physiologically relevant NMDA receptors. O'Brien and Fischbath (1986) found 1 mM APV to be sufficient to eliminate the voltage-dependent component of the response to 1 mM glutamate on chick spinal motoneurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the binding data of Olverman et al (1984) suggest that the affinity of glutamate for D-APV binding sites approaches that of D-APV itself, we think it likely that these high concentrations of APV or D-APV effectively blocked 500 PM glutamate from activating most of the physiologically relevant NMDA receptors. O'Brien and Fischbath (1986) found 1 mM APV to be sufficient to eliminate the voltage-dependent component of the response to 1 mM glutamate on chick spinal motoneurons.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA-activated membrane channels are thought to exhibit a number of special properties, including susceptibility to blockade by magnesium at hyperpolarized membrane potentials Nowak et al, 1984), rapid desensitization (Zorumski and Fischbach, 1985), and high calcium permeability Mayer et al, 1986). Although glutamate has a high affinity for the NMDA receptor (Olverman et al, 1984) magnesium blockade (at least near resting membrane potentials) and desensitization probably act to limit the contribution of NMDA channels, relative to that of QUIS and RAIN channels, to glutamate neuroexcitation. Glutamate neuroexcitation is thus completely blocked by high concentrations of broad spectrum antagonists such as kynurenate (Ganong et al, 1983;Jahr and Jessel, 1985;Huettner and Baughman, 1986) but is only partially attenuated by selective NMDA antagonists (Watkins and Evans, 1981;O'Brien and Fischbach, 1986).…”
mentioning
confidence: 99%
“…If G1 receptors have a relatively high affinity for glutamate (19), a response that slowly rises and decays implies that there might be a 'significant population of extrasynaptic receptors.…”
Section: Methodsmentioning
confidence: 99%
“…D-PSer had a K1 of 303 pM in the same assay. Olverman et al (1984Olverman et al ( , 1988 showed L-PSer to be a weak inhibiter of D- [3H]2-amino-5-phosphonopentanoiC acid (AP5) with an Ki of approx 1 mM. Likewise, Murphy et -al.…”
Section: Binding Studiesmentioning
confidence: 96%